The Influence Of Personality, Discipline And Emotional Intelligence On Employee Performance At The Agriculture And Fisheries Department Of Lebong District - Ghiyats Ferdiatma; Ida Anggriani; Yun Fitriano (Penerbit Jurnal Indonesia, 2024)
The aim of this research is to determine the influence of personality, discipline and emotional intelligence at work on employee performance at the Lebong Regency Agriculture and Fisheries Service. The sample in this study was all employees at the Lebong Regency Agriculture and Fisheries Service who had become ASN, totaling 76 employees. Data were collected using a questionnaire and the analysis methods used were multiple linear regression, determination tests and hypothesis tests. The results of the multiple regression test show a positive direction with the regression equation Y = 7.565 + 0.178X1 + 0.354 X2 + 0.311X3. Variable X1 (Personality) has a significant effect on Y (performance). This can be seen from the significance value of 0.045 <0.05, so it can be concluded that hypothesis 1 is accepted. The variable X2 (Discipline) has a significant effect on Y (performance). This can be seen from the significance value of 0.000 < 0.05. then it can be concluded that hypothesis 2 is accepted. Variable X3 (emotional intelligence) has a significant effect on Y (performance). This can be seen from the significant value of 0.001 < 0.05, so it can be concluded that hypothesis 3 is accepted. Simultaneous test results show that H0 is rejected and Ha is accepted, between the independent variables, namely X1 (personality), X2 (discipline), smaller than 0.05.